2022
DOI: 10.1108/wje-03-2021-0168
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis and control of cracked beam using finite element method by using ANSYS

Abstract: Purpose The purpose of this paper is to develop an organized structure for damage detection of a cracked cantilever beam using finite element method and experimental method technique. Design/methodology/approach Due to presence of cracks the dynamic characteristics of structure change. The change in dynamic behavior has been used as one of the criteria of fault diagnosis for structures. Major characteristics of the structure which undergo change due to presence of crack are: natural frequencies, the amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Liu et al [35] have suggested the finite element method to analyze damaged rotor shafts for the control of crack propagation. Toke and Patil [36] have proposed the finite element method and experimental method technique to identify and control the open crack in the beam.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [35] have suggested the finite element method to analyze damaged rotor shafts for the control of crack propagation. Toke and Patil [36] have proposed the finite element method and experimental method technique to identify and control the open crack in the beam.…”
Section: Introductionmentioning
confidence: 99%